DETERMINAN FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN - Gading Stephanus L. Tobing; Hannes Bakti Manurung; Hengky Pranata Sidabutar; Michael Pariwara Sianipar; Namira Ufrida Rahmi (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the influence of the factors that influence stock prices in food and beverage companies listed on the Indonesia Stock Exchange. Factors that influence include solvency, profitability, liquidity, and company size during the period from 2017 to 2020. The research method used is a quantitative approach with an explanatory nature, using secondary data derived from the company's financial statements. The sampling technique used purposive sampling so that the research sample totalled 14 companies. Data analysis using SPSS software version 25 and multiple linear regression methods. The results showed that partially the profitability and liquidity variables had an effect on the stock prices of food and beverage companies. Meanwhile, the solvency and company size variables have no effect on the stock prices of food and beverage companies listed on the Indonesian stock exchange for the 2017-2020 period. Simultaneously, the variables of solvency, profitability, liquidity, and company size affect the company's stock price with an adjusted R square value of 0.336 or 33.6%.